2008
DOI: 10.1097/bcr.0b013e31818b9e29
|View full text |Cite
|
Sign up to set email alerts
|

Burn Injuries Related to Liquefied Petroleum Gas-Powered Cars

Abstract: Liquefied petroleum gas (LPG), which is used as a type of fuel, is stored as a liquid under high pressure in tanks. Immediate and sudden explosion of these tanks can release a large amount of gas and energy into the environment and can result in serious burns. In this study, the cases of 18 patients injured due to LPG burns in five incidents were examined, along with their epidemiologic features. The authors also investigated the causes of the LPG tank explosions. Inhalation injury was present in 11 cases with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Liquefied petroleum gas (LPG) is used extensively in domestic, agricultural and industrial purposes, with Australia's production expected to increase by 50% in the next 10 years 1 . Although the risk of injury because of ignition or explosion of LPG is well recognized, there have been only a few reports of cold burns related to LPG exposure 2–8 . LPG is a fuel obtained from crude oil during petroleum processing and is a mixture of commercial butane and propane gases, usually in a ratio of 60:40.…”
Section: Introductionmentioning
confidence: 99%
“…Liquefied petroleum gas (LPG) is used extensively in domestic, agricultural and industrial purposes, with Australia's production expected to increase by 50% in the next 10 years 1 . Although the risk of injury because of ignition or explosion of LPG is well recognized, there have been only a few reports of cold burns related to LPG exposure 2–8 . LPG is a fuel obtained from crude oil during petroleum processing and is a mixture of commercial butane and propane gases, usually in a ratio of 60:40.…”
Section: Introductionmentioning
confidence: 99%
“…Various injury mechanisms have been described because of the weakening of a tank's walls, crashes impacting the tank, and tank leakages. Bozkurt et al 4 have reported on safety standards for such tanks in Turkey. It burns more cleanly than petrol or diesel.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports about burns caused by explosion of the LPG tanks, [4] but dangers of cold burns from LPG must also be taken into account. [5] Our patient was a teacher and had no knowledge about the cooling effect of the autogas, and thus did not take any preventive measure like wearing gloves while trying to repair the car.…”
Section: Discussionmentioning
confidence: 99%